2021
DOI: 10.3389/fimmu.2020.623052
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3 Fatty Acid and Skin Diseases

Abstract: Humans are exposed to various external environmental factors. Food intake is one of the most influential factors impacting daily lifestyle. Among nutrients obtained from foods, omega-3 polyunsaturated fatty acids (PUFAs) have various beneficial effects on inflammatory diseases. Furthermore, omega-3 PUFA metabolites, including resolvins, are known to demonstrate strong anti-inflammatory effects during allergic and inflammatory diseases; however, little is known regarding the actual impact of these metabolites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 117 publications
1
29
0
Order By: Relevance
“…Omega-3 fatty acids are present in fish oils and nuts [ 117 ]. Omega-3 fatty acids and their metabolites have potential anti-inflammatory action in inflammatory skin diseases [ 117 , 118 , 119 , 120 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Omega-3 fatty acids are present in fish oils and nuts [ 117 ]. Omega-3 fatty acids and their metabolites have potential anti-inflammatory action in inflammatory skin diseases [ 117 , 118 , 119 , 120 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Omega-3 fatty acids are present in fish oils and nuts [ 117 ]. Omega-3 fatty acids and their metabolites have potential anti-inflammatory action in inflammatory skin diseases [ 117 , 118 , 119 , 120 ]. Purpura is not a typical form of inflammatory skin disease, but causes inflammation in the blood vessels.…”
Section: Treatmentmentioning
confidence: 99%
“…A fatty acid is a carboxylic acid with a long aliphatic chain, which is either a saturated or unsaturated fatty acid [ 6 ]. Fatty acids are important dietary sources of fuel for animals and are essential structural components for cells.…”
Section: The Daily Lifestyle Associated With the Cutaneous Malignanciesmentioning
confidence: 99%
“…Among these environmental factors on Earth, daily lifestyle is a fundamental part of human life and influences human health. For instance, the influence of lifestyles, such as dietary foods and luxury consumptions, accumulates daily and affects human health [ 4 , 5 , 6 ]. Therefore, these influences are helpful information for clinicians to understand the detailed molecular pathogenesis of daily lifestyle-related human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…DHA is enriched in the brain at up to 15% of the total fatty acid (FA) pool and has been shown to be essential for neuronal and retinal development and function [ 1 ]. Studies have shown that the consumption of LC omega-3 oil also helps prevent heart disease, neural disorders, arthritis, asthma, and skin diseases in humans [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%